Searching for a Putative Mechanism of RIZ2 Tumor-Promoting Function in Cancer Models - Rienzo, Monica; Sorrentino, Anna; Di Zazzo, Erika; Di Donato, Marzia; Carafa, Vincenzo; Marino, Maria Michela; De Rosa, Caterina; Gazzerro, Patrizia; Castoria, Gabriella; Altucci, Lucia; Casamassimi, Amelia; Abbondanza, Ciro (Frontiers in Oncology, 2021)
Positive Regulatory Domain (PRDM) gene family members commonly express two main molecular variants, the PR-plus isoform usually acting as tumor suppressor and the PR-minus one functioning as oncogene. Accordingly, PRDM2/RIZ encodes for RIZ1 (PR-plus) and RIZ2 (PR-minus). In human cancers, genetic or epigenetic modiﬁcations induce RIZ1 silencing with an expression level imbalance in favor of RIZ2 that could be relevant for tumorigenesis. Additionally, in estrogen target cells and tissues, estradiol increases RIZ2 expression level with concurrent increase of cell proliferation and survival. Several attempts to study RIZ2 function in HeLa or MCF-7 cells by its over-expression were unsuccessful, maybe for a potential lethal effect in such models. Thus, we over-expressed RIZ2 in HEK-293 cells, which are both RIZ1 and RIZ2 positive but unresponsive to estrogens. The forced RIZ2 expression increased cell viability and growth, prompted the G2-to-M phase transition and organoids formation. Accordingly, microarray analysis revealed that RIZ2 regulates several genes involved in mitosis. Consistently, RIZ silencing in both estrogen-responsive MCF-7 and –unresponsive MDA-MB-231 cells induced a reduction of cell proliferation and an increase of apoptosis rate. Our findings add novel insights on the putative RIZ2 tumor-promoting functions, although additional attempts are warranted to depict the underlying molecular mechanism.